Individual haplotyping of whale sharks from seawater environmental DNA. (16th July 2021) - Dugal, Laurence; Thomas, Luke; Jensen, Mads Reinholdt; Sigsgaard, Eva Egelyng; Simpson, Tiffany; Jarman, Simon; Thomsen, Philip Francis; Meekan, Mark
Abstract: Population genetic data can provide valuable information on the demography of a species. For rare and elusive marine megafauna, samples for generating the data are traditionally obtained from tissue biopsies, which can be logistically difficult and expensive to collect and require invasive sampling techniques. Analysis of environmental DNA (eDNA) offers an alternative, minimally invasive approach to provide important genetic information. Although eDNA approaches have been studied extensively for species detection and biodiversity monitoring in metabarcoding studies, the potential for the technique to address population‐level questions remains largely unexplored. Here, we applied "eDNA haplotyping" to obtain estimates of the intraspecific genetic diversity of a whale shark ( Rhincodon typus ) aggregation at Ningaloo reef, Australia. Over 2 weeks, we collected seawater samples directly behind individual sharks prior to taking a tissue biopsy sample from the same animal. Our data showed a 100% match between mtDNA sequences recovered in the eDNA and tissue sample for all 28 individuals sampled. In the seawater samples, >97% of all reads were assigned to six dominant haplotypes, and a clear dominant signal (~99% of sample reads) was recovered in each sample. Our study demonstrates accurate individual‐level haplotyping from seawater eDNA. When DNA from one individual clearly dominates each eDNA sample, it provides many of the same opportunities for population genetic analyses as a tissue sample, potentially removing the need for tissue sampling. Our results show that eDNA approaches for population‐level analyses have the potential to supply critical demographic data for the conservation and management of marine megafauna.